Well-being and academic achievement on students in city of Yogyakarta - Fuad Mubarok; Adi Cilik Pierewan (Jurnal Ecopsy, 2020)
Several studies have suggested the importance of well-being as a predictor of adolescents’ academic achievements. The purpose of this study was to prove the existence of a well-being effect on adolescents’ academic achievement. The subjects of this study were adolescents with a vulnerable age between 14 to 15 years old with 385 respondents as a sample. This study used questionnaires to measure the well-being of adolescents. Data on adolescents’ academic achievement were obtained from students’ scores (GPA). The hypothesis compiled in this research was the effect of well-being on adolescents’ academic achievement. This study used a regression analysis to determine the effect of well-being on adolescents’ academic achievement. The reliability of the instrument was analyzed using Cronbach's Alpha. The results of the research found that well-being can be a predictor of adolescents’ academic achievement.